Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1097/psy.0000000000001133
|View full text |Cite
|
Sign up to set email alerts
|

Through the Looking-Glass: Psychoneuroimmunology and the Microbiome-Gut-Brain Axis in the Modern Antiretroviral Therapy Era

Abstract: Objective: Depression, substance use disorders, and other neuropsychiatric comorbidities are common in people with HIV (PWH), but the underlying mechanisms are not sufficiently understood. HIV-induced damage to the gastrointestinal tract potentiates residual immune dysregulation in PWH receiving effective antiretroviral therapy. However, few studies among PWH have examined the relevance of microbiomegut-brain axis: bidirectional crosstalk between the gastrointestinal tract, immune system, and central nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 161 publications
(208 reference statements)
0
2
0
Order By: Relevance
“…Other hypothesised mechanisms are molecular mimicry to bacterial antigens leading to dysfunctional adaptive immune responses, the production of bacterial metabolites that may directly damage the brain and were supposed to be related to specific neurodegenerative disorders, including Alzheimer's disease, and vagal dysfunction related to HIV-associated autonomic neuropathy, associated with intestinal bacterial overgrowth and changes in immune and gastrointestinal functions [161,[166][167][168]. Moreover, the vagus nerve is essential for reducing intestinal permeability in HIV infection, thus preventing microbial products from penetrating the lamina propria and entering the circulation to amplify the immune dysregulation and inflammation [169]. HIV neuropathogenesis may also occur through the mechanisms of oxidative stress and metabolic disturbances indirectly linked to gut bacterial processes [161], and neuroinflammation is exacerbated by the persistent replication of HIV in CNS unhindered by ART, as the penetrability of these compounds through the blood-brain barrier is variable and incomplete [170].…”
Section: The Brain-gut Axis and Neurocognitive Disordersmentioning
confidence: 99%
“…Other hypothesised mechanisms are molecular mimicry to bacterial antigens leading to dysfunctional adaptive immune responses, the production of bacterial metabolites that may directly damage the brain and were supposed to be related to specific neurodegenerative disorders, including Alzheimer's disease, and vagal dysfunction related to HIV-associated autonomic neuropathy, associated with intestinal bacterial overgrowth and changes in immune and gastrointestinal functions [161,[166][167][168]. Moreover, the vagus nerve is essential for reducing intestinal permeability in HIV infection, thus preventing microbial products from penetrating the lamina propria and entering the circulation to amplify the immune dysregulation and inflammation [169]. HIV neuropathogenesis may also occur through the mechanisms of oxidative stress and metabolic disturbances indirectly linked to gut bacterial processes [161], and neuroinflammation is exacerbated by the persistent replication of HIV in CNS unhindered by ART, as the penetrability of these compounds through the blood-brain barrier is variable and incomplete [170].…”
Section: The Brain-gut Axis and Neurocognitive Disordersmentioning
confidence: 99%
“…This special issue concludes with a review article by Carrico and colleagues ( 39 ) that places these findings in a broader context, focusing on the bidirectional nature of mind-body relationship in the mental health among people living with HIV. The interrelationships between established psychoneuroimmunologic mechanisms and microbiome-gut-brain axis interactions are highlighted with recommendations for future biobehavioral research to investigate the bidirectional pathways linking the biological and behavioral processes with mental health in PWH.…”
mentioning
confidence: 93%
“…Plasma markers of inflammation and monocyte activation have been linked to cognitive outcomes; however, how this relates to plasma tryptophan and kynurenine is unexplored. 25–29…”
Section: Introductionmentioning
confidence: 99%
“…Plasma markers of inflammation and monocyte activation have been linked to cognitive outcomes; however, how this relates to plasma tryptophan and kynurenine is unexplored. [25][26][27][28][29] The tryptophan-kynurenine (TK) pathway has been studied in the context of HIV. A recent review found increased IDO activation (using K:T ratio as a surrogate marker) is associated with age and chronic inflammation in PWH.…”
Section: Introductionmentioning
confidence: 99%